Developments in the scientific and clinical understanding of autoinflammatory disorders - Lachmann, Helen J (BioMed Central, 2009)
The autoinflammatory diseases, also known as periodic fever syndromes, are disorders of innate immunity which can be inherited or acquired and which cause recurrent, self-limiting, seemingly spontaneous episodes of systemic inflammation and fever in the absence of autoantibody production or infection. There has been much recent progress in elucidating their aetiologies and treatment. With the exception of familial Mediterranean fever, which is common in certain populations, autoinflammatory diseases are mostly rare but should not be overlooked in the differential diagnosis of recurrent fevers since DNA diagnosis and effective therapies are available for many of them.